PENGARUH MOTIF PENGGUNAAN MEDIA DAN KUALITAS INFORMASI AKUN @JKTINFO SEBAGAI MEDIA BERITA ONLINE TERHADAP PEMENUHAN KEBUTUHAN INFORMASI MASYARAKAT KOTA JAKARTA (Survei Pada Pengikut Instagram Akun @jktinfo) - Rizkika Novia Ramadhanti (2022)
Basically, humans will choose for themselves which media they will choose to get information, based on several considerations, such as how the benefits will be obtained when using the media and how much effort must be made to use the media. This also happens to Instagram social media users who use the media for various things. Users of the Instagram social media platform have a variety of motives and needs that differ from one another. This study aims to examine the Uses and Gratifications theory by knowing whether there is an influence on the motives for using media and the quality of the @jktinfo account information as an online news media on meeting the information needs of the people of Jakarta. Through this research, it is also known how much influence the independent variable has on the dependent variable. The method used is a quantitative approach with the type of explanatory research. The population in this study are followers of the @jktinfo account, which totaled 2.7 million in October 2021. Then the sample taken using the Taro Yamane formula was 100 people. Data analysis was carried out using the SPSS 25 program by conducting validity tests using factor analysis techniques, reliability tests, classical assumption tests, regression analysis, correlation tests, and hypothesis testing. The final result of the study shows that the motive for using media and the quality of information has an influence on meeting the information needs of the people of Jakarta. The study showed a significance value on the t-test <0.05, which means that Ha1 and Ha2 were accepted. The relationship between the three variables was stated to be in the category of a very strong relationship with an R value (Correlation Coefficient) of 0.833. This means that the motives of each user and the information shared on the @jktinfo account has a relationship with the fulfillment of the information needs of the followers of the Instagram account. In this study, the variables of media use motives and information quality have a joint effect of 68.8% on the variable of meeting information needs and the remaining 31.2% is influenced by other variables outside of this study.